Bung Karno : di antara saksi dan peristiwa - Farrel M. Rizqy (Jakarta : Penerbit Buku Kompas, 2009)
Essays on political views and life of Soekarno, the first Indonesian President.
Includes index.
Mengandungi rujukan bibliografi (p.177-178) dan indeks.
Teks dalam Bahasa Indonesia.
Keywords: Soekarno, -- 1901-1970.; Indonesia -- Politics and government